Half a Century with the Space Structures Research Centre of the University of Surrey. Issue 4 (December 2014) - Behnejad, S. Alireza; Parke, Gerard A. R.
The Space Structures Research Centre was founded by Professor Zygmunt Stanislaw Makowski in 1963. The Centre is a part of the Department of Civil and Environmental Engineering of the University of Surrey, Guildford, UK. Many different activities have been organised by the Centre since its establishment in areas such as research, publication, teaching, organisation of conferences, as well as, consulting work. This paper outlines the activities of the Centre in the past 50 years and gives an overview of the role of the Centre in the development of spatial structures in the world.